Radiative cooling for dew condensation. (June 2021) - Trosseille, Joachim; Mongruel, Anne; Royon, Laurent; Beysens, Daniel
Highlights: Radiative cooling chamber creates conditions of controlled natural dew production. Monitoring dew phenomenon helps understanding its formation for quantitative studies. Design of a device with measurement sensors allow quantitative data to be obtained. Radiative cooling power of 50 W . m − 2 is achieved. Condensation rate of about 4 × 10 − 5 g . s − 1 is measured in the device. Graphical abstract: Abstract: We describe a radiative cooling chamber which reproduces in the laboratory radiative cooling and subsequent dew formation. Based on radiative exchange with a cold source (at a temperature of nearly -80 °C), which acts as a cold black body, cooling power of at least 50 W.m -2 is achieved. Radiative exchange is quantitively estimated. This original device permits to study under controlled air temperature and humidity the formation of dew on any system (material, biological) for which contact cooling is inefficient, and in particular investigate the influence of radiative and wetting surface properties on dew yield. It is applicable to the study of dew itself and its effects on plants and small animals, as well as dew atmospheric chemistry, and more generally of any natural radiative cooling application.